Suitability of pitaya fruit fermented by sourdough LAB strains for bread making: its impact on dough physicochemical, rheo-fermentation properties and antioxidant, antifungal and quality performance of bread - Jacob Ojobi Omedi (Elsevier, 2021)
The objective of this study was to investigate the suitability of incorporating pitaya fruit fermented by antifungal LAB strains Lactiplantibacillus plantarum and Pediococcus pentosaceus at 1: 30 °C for 24h or 2: 31 °C for 19.5h as an ingredient with respect to bread making performance and bio-preservation effect. Underlying mechanisms related to gluten protein hydrolysis, starch hydrolysis, and yeast activity in dough were explored. The antioxidant activity, antifungal activity and bread making performance of the resulted breads were analyzed. Also, the antifungal phenolic acids in the breads were identified and quantified. Incorporation of fermented substrates in dough increased yeast activity and gas production capacity, but decreased gas retention capacity. This was attributed to increased dough acidity after incorporating fruit substrates. As a result, reducing sugar and free sulfhydryl (SH) groups increased in these doughs which indicated higher starch and gluten protein hydrolysis, respectively. However, SH groups increased at lower rate in presence of substrates fermented by L. plantarum and P. pentosaceus at condition 2 than 1. This could be due to improvement of gluten network as revealed by decreased α-helix (%) and increased β-turn (%) in secondary gluten structures in these doughs which subsequently resulted in more homogeneous microstructural properties than in presence of unfermented substrate compared to wheat dough. Subsequently, bread specific volume increased (6.6–20.0%) in presence of fermented substrates, especially fermented by L. plantarum at (2). Moreover, bread incorporated with fermented substrates (P. pentosaceus than L. plantarum at 1 than 2) had enhanced antioxidant activities, lower fungal growth rates based on challenge tests and mold free shelf life. Antifungal phenolic acids such as gallic acids, caffeic acid, protocatechuic acid were only detected in bread incorporated with fruit substrates, and their total content higher in fermented substrates.